The Myxobacterium Myxococcus xanthus Can Sense and Respond to the Quorum Signals Secreted by Potential Prey Organisms - Lloyd, Daniel G.; Whitworth, David E. (Frontiers in Microbiology, 2017)
The myxobacterium Myxococcus xanthus is a predatory member of the soil microfauna, able to consume bacteria (Gram-negative, Gram-positive), archaea and fungi. Many potential prey of M. xanthus communicate amongst themselves using acyl homoserine lactones (AHLs) as quorum signals. M. xanthus cannot itself produce AHLs, but could potentially benefit by responding to exogenous AHLs produced during signalling between proximal prey. Four AHLs of different side chain length were tested and all found to delay sporulation of M. xanthus vegetative cells, and to stimulate germination of myxospores, increasing the proportion of predatory vegetative cells in the population. The predatory activity and expansion rates of M. xanthus colonies were also found to be stimulated by AHLs. Thermally inactivated AHLs had no effect on M. xanthus cells, and the response to AHLs depended (non-linearly) on the length of AHL side chain, suggesting that the effect of AHLs was mediated by specific signalling within M. xanthus, rather than being a consequence of the chemical or physical properties of AHLs. Therefore, it seems that the presence of xenic quorum signalling molecules enhances the predatory activity of M. xanthus. AHLs increase the proportion of the population capable of predation, and stimulate the motility and predatory activity of vegetative cells. We therefore propose that in the wild, M. xanthus uses AHLs as markers of nearby prey, potentially eavesdropping on the conversations between potential prey organisms.